Television in Kheda : a social evaluation of SITE - Agrawal, Binod C.; Malek, M. R.; Patel, Madhu (New Delhi : Concept Pub. Co., 1986)
Study conducted in Dadusar, Kheda District, Gujarat, from July 1975 to October 1976.
Includes index.
Bibliography: p. [75]
Keywords: Satellite Instructional Television Experiment (India); Television broadcasting -- Social aspects -- India -- Dadusar; Dadusar (India)